Rabbit PrP Is Partially Resistant to in vitro Aggregation Induced by Different Biological Cofactors - Angelli, Juliana N.; Passos, Yulli M.; Brito, Julyana M. A.; Silva, Jerson L.; Cordeiro, Yraima; Vieira, Tuane C. R. G. (Frontiers in Neuroscience, 2021)
Prion diseases have been described in humans and other mammals, including sheep, goats, cattle, and deer. Since mice, hamsters, and cats are susceptible to prion infection, they are often used to study the mechanisms of prion infection and conversion. Mammals, such as horses and dogs, however, do not naturally contract the disease and are resistant to infection, while others, like rabbits, have exhibited low susceptibility. Infection involves the conversion of the cellular prion protein (PrPC) to the scrapie form (PrPSc), and several cofactors have already been identified as important adjuvants in this process, such as glycosaminoglycans (GAGs), lipids, and nucleic acids. The molecular mechanisms that determine transmissibility between species remain unclear, as well as the barriers to transmission. In this study, we examine the interaction of recombinant rabbit PrPC (RaPrP) with different biological cofactors such as GAGs (heparin and dermatan sulfate), phosphatidic acid, and DNA oligonucleotides (A1 and D67) to evaluate the importance of these cofactors in modulating the aggregation of rabbit PrP and explain the animal’s different degrees of resistance to infection. We used spectroscopic and chromatographic approaches to evaluate the interaction with cofactors and their effect on RaPrP aggregation, which we compared with murine PrP (MuPrP). Our data show that all cofactors induce RaPrP aggregation and exhibit pH dependence. However, RaPrP aggregated to a lesser extent than MuPrP in the presence of any of the cofactors tested. The binding affinity with cofactors does not correlate with these low levels of aggregation, suggesting that the latter are related to the stability of PrP at a low pH. The absence of the N-terminus affected the interaction with cofactors, influencing the efficiency of aggregation. These findings demonstrate that the interaction with polyanion cofactors is related to rabbit PrP being less susceptible to aggregation in vitro and that the N-terminal domain is important to the efficiency of conversion, increasing the interaction with cofactors. The decreased effect of cofactors in rabbit PrP likely explains its lower propensity to prion conversion.